Sarafina! - Singh, Anant, 1956-; Roodt, Darrell; Goldberg, Whoopi, 1955-; Makeba, Miriam; Kani, John.; Ngema, Mbongeni; Khumalo, Leleti; Lions Gate Home Entertainment; Hollywood Pictures; Miramax Films (Toronto, Ontario : Lions Gate Home Entertainment, 2001)
In a world where truth is forbidden, an inspiring teacher dares to instill in her students lessons not found in schoolbooks. In doing so, she challenges their freedom and hers
15502E
Musical; songs in English and Zulu
A Distant Horizon and Ideal Films presentation in association with Videovision Enterprises, Les Films Ariane, Vanguard Films and the BBC
Based on the play by Mbongeni Ngema
Videodisc release of the 1992 motion picture
Producer, Anant Singh; writers, William Nicholson, Mbongeni Ngema; photography, Mark Vicente; production designer, David Barkham; editors, Peter Hollywood, Sarah Thomas; music and lyrics, Mbongeni Ngema; additional songs, Hugh Masekela; music score, Stanley Meyers
Keywords: Apartheid -- South Africa -- Drama; Musical films; Feature films; Video recordings; Drama